Ekstrak Buah Delima sebagai Alternatif Terapi Recurrent Apthous Stomatitis (RAS) - Hernawati, Sri (Fakultas Kedokteran Gigi Universitas Jember, 2015)
AbstractRecurrent aphthous stomatitis (RAS) is an oral mucosal lesion in the form of asingle or multiple recurrent ulcer. The etiology is still not known, usually occurs in thesecond decade. RAS is more likely to strike in early adulthood with a tendency moreoften in women than men (3:1). The RAS precipitating factors are infection, trauma,hormones, emotional effect, fatigue, immunological disorders, nutritional disorders,and hereditary. Clinically RAS is in the form of ulcers that are round, single ormultiple, varying in diameter, white-centered, redness in the edge, and painful. The RASClassification: aphthous ulcers major, minor aphthous ulcers and herpetic form.Ulceration is a mucosal damage to the stratum basale, painful and interfere whilechewing food. RAS can heal itself between 7-14 days and even more but theexcruciating pain will torture the patient. Wound healing is a complex process thatinvolves many elements which work in sync to achieve wound healing. Pomegranate isone of the widely studied medicinal plants for health. Pomegranate has benefits as antiinflammatory,anti-oxidant, anti-microbial, immunostimulatory, cheap, easy to obtain,have no side effects. Pomegranate has very complex potential that can eliminate variouspredisposing factors in a single therapy and also can increase endurance. Based on thisfact the purpose of this research is to theoretically study pomegranate as an alternativetherapy for RAS biomolecularly. The conclusion is the active ingredient of pomegranatetheoretically has the functions of anti-inflammatory, anti-oxidant, anti-microbial,immune-stimulatory and can regulate the fibrosis process, so that pomegranate cancure RAS.Keywords: RAS, pomegranate, healing process.